Narrative intelligence in nursing: Storying patient lives in dementia care. Issue 3 (29th April 2018) - Witham, Gary; Haigh, Carol
Abstract : This paper examines narrative approaches to care within the context of dementia. It reviews the function of stories and explores some of the narrative genres that shape the cultural perceptions of dementia. We argue that narrative intelligence within healthcare is an important element in nurturing communal self‐identity for people living with dementia. Listening and responding to stories and the cultural framework that this encompasses is an embodied action that is not just related to cognitive recall but situates us within a cultural community. People with dementia may have challenges in maintaining narrative legitimacy in the face of fractured stories and incoherent narratives. Health professionals can offer support in reframing and presenting counterstories that maintain identities that can potentially be marginalised, silenced and open to narrative foreclosure. This process requires health professionals to be attentive and responsive to how patients with dementia and their supporters construct and position the stories they tell and the meaning(s) they attach to them.